2004
DOI: 10.1074/jbc.m306960200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Role of Protein Kinase Cδ Isoform in Agonist-induced Dense Granule Secretion in Human Platelets

Abstract: Several platelet agonists, including thrombin, collagen, and thromboxane A 2 , cause dense granule release independently of thromboxane generation. Because protein kinase C (PKC) isoforms are implicated in platelet secretion, we investigated the role of individual PKC isoforms in platelet dense granule release. PKC␦ was phosphorylated in a time-dependent manner that coincided with dense granule release in response to protease-activated receptor-activating peptides SFLLRN and AYPGKF in human platelets. Only ago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
132
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(144 citation statements)
references
References 65 publications
11
132
1
Order By: Relevance
“…6A). On the other hand, there were no significant attenuations by 1 M Gö6976, an inhibitor of PKC-␣ and PKC-␤ (Ma et al, 2002), or 1 M rottlerin, an inhibitor of novel types of PKCs, including the PKC-␦ isoform (Murugappan et al, 2004). These results suggest that PKC-␥ is more likely to be involved in insulin-induced necrosis inhibition.…”
Section: Pkc-␥ Activation In Insulin Signaling Prevents Necrosis 1029mentioning
confidence: 49%
See 1 more Smart Citation
“…6A). On the other hand, there were no significant attenuations by 1 M Gö6976, an inhibitor of PKC-␣ and PKC-␤ (Ma et al, 2002), or 1 M rottlerin, an inhibitor of novel types of PKCs, including the PKC-␦ isoform (Murugappan et al, 2004). These results suggest that PKC-␥ is more likely to be involved in insulin-induced necrosis inhibition.…”
Section: Pkc-␥ Activation In Insulin Signaling Prevents Necrosis 1029mentioning
confidence: 49%
“…To clarify the PKC isoform that plays an important role in necrosis inhibition, we performed pharmacological analysis using a panel of different PKC inhibitors (Ma et al, 2002;Murugappan et al, 2004). As shown in Fig.…”
Section: Pkc-␥ Activation In Insulin Signaling Prevents Necrosis 1031mentioning
confidence: 99%
“…Interestingly, previous work has demonstrated that collagen-evoked Ca 2+ signalling in human platelets is negatively regulated by novel PKC isoforms and positively regulated by conventional PKC isoforms [44]. An agonist-specific effect of isoform-selective PKC inhibition has also been reported for platelet dense granule secretion [45]. These results beg the question as to whether novel PKC isoforms are potentiating collagen-evoked signalling by triggering the same effects on SERCA and Na + /K + -ATPase activity elicited by the conventional isoforms upon thrombin-or ADP-stimulation, or whether there are distinct molecular targets for PKC that modulate collagen-evoked Ca 2+ signals.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, positive regulation by PKC␦ of stimulus-induced granule secretion has been described in nonimmune cell types. PKC␦ was proposed to have a role in the induction of dense granule and insulin secretion in platelets and pancreatic ␤ cells, respectively (38,39). Interestingly, depending on the type of stimulus, PKC serves either as a positive or as a negative regulator of dense granule secretion in platelets.…”
Section: Discussionmentioning
confidence: 99%